Late onset of microbial keratitis after laser in situ keratomileusis surgery: case series. Issue 8 (August 2021) - Garcerant, Daniel; Cabrera-Aguas, Maria; Khoo, Pauline; Watson, Stephanie L.
Abstract : Late-onset microbial keratitis in patients with previous LASIK had a similar clinical course to non-LASIK keratitis, such that the surgery may not have been a risk factor for infection. Abstract : Purpose: To report predisposing factors, clinical features, microbiology spectrum, antibiotic resistance, antimicrobial therapy, and outcomes of patients with a previous laser in situ keratomileusis (LASIK) surgery and diagnosed with presumed microbial keratitis. Setting: Sydney Eye Hospital, Sydney, New South Wales, Australia. Design: Retrospective case review. Methods: Patients were identified from pathology and hospital coding data from 2012 to 2016. Inclusion criteria were all patients with a previous LASIK surgery, a presumed diagnosis of microbial keratitis, and a corneal scrape performed and aged older than 18 years. Demographics, clinical details, and outcomes were collated from the medical records. Results: Sixteen patients were included, with median age of 41.5 years (range 22 to 85 years) and 56.2% of women. The median time between LASIK procedure and microbial keratitis presentation was 38.3 months (interquartile range 6.7 to 77.45 months). Cultures were positive for bacteria in 12 (75%) of 16 scrapes. Of the bacterial isolates, 12 (85.7%) were gram-positive and 2 (14.3%) gram-negative. Sensitivity profiles for the isolated bacteria were similar between fortified antibiotics (cefalotin and gentamicin) and commercial products (chloramphenicol and ofloxacin). Complications included the need for tectonic grafts, nonhealing epithelial defects, thinning, and neovascularization. Conclusions: Late onset of keratitis after LASIK can occur with no positive cultures for nontuberculous mycobacteria, no interface involvement, and no other usual features reported in case series of infectious keratitis in LASIK patients. It has a similar clinical course to non-LASIK keratitis, such that the surgery may not have been a risk factor for infection.